Nonsmooth optimization over the (weakly or properly) Pareto set of a linear-quadratic multi-objective control problem: Explicit optimality conditions - Bonnel, Henri; Pham, N. (2011)
We present explicit optimality conditions for a nonsmooth functional dened over the (properly or weakly) Pareto set associated with a multiobjective linear-quadratic control problem. This problem is very dicult even in anite dimensional setting, i.e. when, instead of a control problem, we deal with a mathematical programming problem. Amongst various applications, our problem may be considered as a response for a decision maker when he has to choose a solution over the solution set of the grand coalition p-player cooperative differential game.